A review on acid and enzymatic hydrolyses of sago starch - Azmi, Azlin Suhaida; Abdul Malek, Mohd Izhar; Mohamad Puad, Noor Illi (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
This paper reviews reported studies on the hydrolysis of starch especially sago via acid and enzyme. The review begins with overview of sago palm and the starch industry, followed by process of extracting the starch from sago pith. Physicochemical properties of sago starch were tabulated for better understanding of hydrolysis process. Factors or process condition influencing hydrolysis process is discussed based on results from previous researches. Advantages and disadvantages of each hydrolysis is also discussed. Generally, there are very few researches dedicated on sago starch as compared to other starches. It can be concluded that, enzyme hydrolysis gives higher yield at milder process conditions. However, the reaction rate of enzyme hydrolysis is still low compared to acid hydrolysis.